Long-term treatment with α-lipoic acid and myo-inositol positively affects clinical and metabolic features of polycystic ovary syndrome. (1st February 2020) - Fruzzetti, Franca; Fidecicchi, Tiziana; Palla, Giulia; Gambacciani, Marco
Abstract: The aim of this retrospective study was to evaluate the effects of a long-term treatment with α-lipoic acid (ALA) combined with myo-inositol (MI) on clinical and metabolic features of women with polycystic ovary syndrome (PCOS). Fifty-seven women with PCOS and a history of oligoamenorrhea were treated with MI and ALA (800 mg + 2000 mg per day). Forty-four of them had complete clinical charts and were considered eligible for the study. Information about cycle length and body mass index (BMI) was checked after 6, 12, and 24 months. After 12 months ovarian volume, total testosterone plasma levels and changes in hirsutism were also evaluated. The metabolic parameters were evaluated in 16 women after 6 and 18 months of the treatment. Cycle length was significantly reduced at 6 (p < .001), 12, and 24 months of treatment (p < .01). BMI showed a reduction only at 6 months (p < .05), thereafter returning similar to the basal values. No changes of testosterone and ovarian volume were observed. HOMA-IR and fasting insulin were unchanged, but the insulin response to a 3 h OGTT was improved after 6 (p < .01) and 18 months (p < .05) of treatment. No individual suffered from any adverse event. In conclusion, the combination of ALA and MI showed to be useful as long-term therapy in PCOS women, providing a normalization of the menstrual cycle and an amelioration of insulin levels with a high tolerability.